The Relationship Between Knowledge and Attitudes with External Genital Hygiene Practices in Female - Sumiati, Sumiati; Ratanto, Ratanto; Wahyuni, Rahmawati; Sapto Pramono, Joko (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: In this era of growing information, the knowledge, and attitudes that high school girls have towards external genitalia hygiene practices are very important. Adequate knowledge about the importance of keeping the genital area clean can help schoolgirls prevent infections and related health problems. In addition, a good attitude towards external genitalia hygiene practices also affects their daily habits in maintaining personal hygiene. In this context, the relationship between schoolgirls' knowledge and attitude is closely related to external genitalia hygiene practices. Objective: Knowing the relationship between knowledge and attitudes with external genital hygiene practices in female students at Mahakam Laham High School, Mahakam ulu District in 2023. Methods: Correlational design design with a cross sectional approach. Sampling using total sampling technique with a sample size of 40 people. Results and Discussion: Most of the knowledge about external genital hygiene is not good as many as 21 (52.5%) people. Most of the attitudes towards external genital hygiene are negative as many as 22 (55%) people. Most of the external genital hygiene practices are not good as many as 22 (55%) people. The results of the Chi-Square statistical test obtained a value of p = 0.002. Conclusion: There is a relationship between knowledge and external genital hygiene practices in female students at Mahakam Laham High School, Laham District, Mahakam Ulu Regency in 2023